Cognitive assessment of older adults at the acute care interface: the informant history. Issue 1087 (19th January 2016) - Dyer, Adam H; Nabeel, Shamis; Briggs, Robert; O'Neill, Desmond; Kennelly, Sean P
Abstract: Purpose of the study: An informant history is critical in the complete cognitive assessments of older adults, but has never been formally assessed. Study design: A convenience sample of older adults aged ≥70 years were assessed using cognitive screeners for delirium (confusion assessment method-intensive care unit) and dementia (standardised Mini Mental State Examination and AD8) in a tertiary referral emergency department (ED). Results: A total of 220/270 (81.5%) adults were included in the study (mean age 78.8±6.16; 49.1% male). Informant histories, obtained in almost two-thirds (61.1%, 66/108) of patients where desired, revealed a cognitive pattern suggestive of previously undiagnosed dementia in 39.4% (26/66). Most informants were relatives/friends (93.9%, 62/66) and were rated very good/excellent in contribution to care (96.9%, 64/66) and ability to provide useful information (93.9%, 62/66). The acute environment was also rated suitable to brief informant interviewing (mean duration <6 min) in terms of privacy (8.4±1.6/10) and accessibility (8.5±1.47/10). Following a review of the attending ED physician's notes, an informant history (either obtained/desired/refused) was only documented in 5.6% of cases. Conclusions: The informant history represents a much underused tool in the cognitive assessment of older adults presenting to the ED. The main barrier to informant interviewing in the ED environment appears to be informant availability. Where available, the informant history is easy to extract and provides invaluable information to the assessing physician. The acute care environment is suitable to brief informant interviews using readily available frameworks (AD8). However, the informant history is rarely obtained in this context, and further emphasis on undergraduate and postgraduate medical curricula is warranted.